Pemanfaatan Talking Stick dalam Pengembangan Media Pembelajaran Bahasa Interaktif - Siti Chodijah Nur Indah Berliani; Septi Gumiandari (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
The talking stick learning system involves the use of a talking stick as a means of facilitating dialogue in groups. This learning media helps students' involvement and responsiveness and increases social interaction in the learning process. By utilizing this innovative approach, the research aims to increase the interaction and involvement of students and teachers in the language learning process and its correlation with Islam. The research method used is a qualitative approach with a case study research design. The research results show that the use of talking sticks significantly increases students' active participation and learning motivation and contributes to the development of more interactive and effective language learning strategies.